Relay-cropping soybean-maize in saturated soil culture increases efficiency of land use and nitrogen fertilizer - Suntari; Ghulamahdi, Munif; Maya Melati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
Relay-cropping in saturated soil cultivation could increase land efficiency, but its effect on land use and nitrogen fertilizer efficiency is unclear. The research objective was to evaluate the land productivity of the relay-cropping system by calculating the land equivalent ratio (LER) and the effectiveness of nitrogen fertilizer, and by determining the effect of previous soybean biomass. The experiment was arranged in a three-factor randomized complete block design. The first factor was the cropping patterns of soybean and maize, i.e., relay-cropping soybean-maize and maize monoculture. The second factor was the maize varieties, i.e., Pioneer 27 and Sukmaraga. The third factor was the application of N fertilizer with 4 doses: 0, 50, 100, and 150 kg ha-1. The results showed that the application of soybean biomass increased maize yield by 7.24%. Pioneer 27 produced a higher yield than Sukmaraga, and the dose of N fertilizer of 150 kg ha-1 resulted in the highest yield of 7.50 tons ha-1. The highest LER of 1.85% was achieved in the relay-cropping by applying N fertilizer 150 kg ha-1. The experiment concludes relay-cropping after soybean save land by about 85% and save N fertilizer by 33.3%. The reduction of N fertilizer application by 33.3% (100 kg N ha-1) reduced corn cob productivity by 13.3%, and is not significantly different from 150 kg N ha-1. Keywords: chlorophyll, LER, plant residue